Motivation to use self-regulated learning strategies in learning management system amongst science and social science undergraduates - Hashemyolia, Shayeshteh; Asmuni, Azizan; Mohd Ayub, Ahmad Fauzi; Mohd Daud, Shaffe; Arif Shah, Jasmin (Canadian Center of Science and Education, 2015)
The purpose of this study is to determine students’ levels of self-regulated learning by adjusting Motivated Strategies for Learning Questionnaire (MSLQ) developed by (Pintrich et al., 1993). This study involved 436 undergraduate students. The validity of instrument used was checked by convergent validity and discriminate validity in Structural Equation Modeling. The reliability of scale was measured by internal consistency analyses whilst students’ levels of self-regulated learning detected by descriptive analyses involving percentage, frequency, means, t-tests and standard deviation . As a result it can be concluded that MSLQ is recognized as a valid and reliable scale in order to examine levels of self-regulated learning among university students in Malaysia. Besides, the students’ self-regulated learning strategies are found to be generally in the middle range; their highest level of skills being Effort regulation, whereas the lowest skill is Metacognitive strategies. The students’ level of self-regulated learning in social sciences faculties was significantly lower than students in science faculties.